Survey on Data Mining Technique Using Decision tree For Hepatitis virus (International Journal of Advanced Research in Computer Science, 2017)
This work demonstrates the application of decision tree, as data mining tool, in the health care system. Data mining has the capabilityfor classification, prediction, estimation, and pattern recognition by using health databases. Databases of health systems contain significantinformation for decision making. It could be properly revealed with the application of appropriate data mining techniques. Decision trees areemployed for identifying valuable information in health databases. In this paper Decision tree as a data mining tools is used for predication thespread types of disease of hepatitis virus in reigns that high affect to people with different temperature and prevention of this disease by usingrules that needed to predicate the diseases .Â Keywords:- Decision Tree Modeling, Healthcare Data Mining Applications, Decision Rule Induction.